Synergistic mechanotherapy and sonopermeation guided by mathematical modeling for solid tumor treatment - Koutsi, Marina; Stylianopoulos, Triantafyllos; Mpekris, Fotios (Frontiers in Drug Delivery, 2025)
The progression of tumors and their response to treatment are significantly influenced by the presence of elevated mechanical solid stress. This solid stress compresses intratumoral blood vessels, leading to reduced blood flow (hypoperfusion) and insufficient oxygen levels (hypoxia), both of which hinder the delivery of oxygen and therapeutic agents. As a result, these conditions promote tumor growth, resistance to treatment, and ultimately undermine the effectiveness of therapies. To address these challenges, strategies like mechanotherapeutics and ultrasound sonopermeation have been developed to enhance blood flow and improve drug delivery to tumors. Mechanotherapy aims to reduce the mechanical stress and stiffness within tumors, helping to decompress vessels and restore normal perfusion. Ultrasound sonopermeation temporarily increases the permeability of blood vessel walls in a non-invasive manner, boosting blood flow and improving the delivery of therapeutic drugs. Here, we developed a mathematical model to explore the combined effects of mechanotherapeutics and sonopermeation on optimizing nano-immunotherapy efficacy. The model integrates complex interactions between key components involved in tumor progression, including tumor cells, immune cells, and vascular elements such as endothelial cells, angiopoietins, and vascular endothelial growth factor. To assess the model’s validity, its predictions for key parameters, including tumor volume, functional vascular density, and hypoxia levels, were compared with experimental data, demonstrating a strong correlation, and confirming the accuracy of the mathematical framework. Furthermore, we carried out a parametric analysis to establish critical guidelines aimed at optimizing both the sequence and timing of experimental procedures. Specifically, we investigated the therapeutic outcomes of two treatment scenarios: applying sonopermeation first, followed by nano-immunotherapy, and vice versa. Also, we determined the optimal time interval between the application of sonopermeation and the commencement of the combined nano-immunotherapy regimen to maximize therapeutic efficacy.